Investigation of the state of virus carrier of newcastle disease in budgerigars (melopsittacus undulatus) - Denadai, Janine [UNESP]; Paulillo, Antônio Carlos [UNESP]; Schmidt, Elizabeth Moreira dos Santos [UNESP]; Martins, Gislaine Regina Vieira [UNESP]; Torres Carrasco, Adriano de Oliveira (My University, 2013)
This study aimed to evaluate the importance of vaccination against Newcastle Disease (ND) in budgerigars (Melopsittacus undulatus) and to investigate the state of carrier of the virus (NDV) in this species. There were used 72 budgerigars distributed into four different experimental groups, vaccinated or not against ND: GI (Ulster 2C strain), GII (B1 strain), GIII (LaSota strain) and GIV (not vaccinated-control). At 11 months of age, all groups of birds were challenged with a pathogenic virus (NDV) suspension, EID50 = 108.15/0.1 mL. A group of Specific-Pathogen-Free (SPF) chickens were used as control of the virus. Cloacal swabs and blood samples were collected after 13 and 19 days post-challenge, respectively, for genome viral excretion by Reverse Transcription Polymerase Chain Reaction (RT-PCR) and antibody's level by the inhibition of hemagglutination test (HI). Budgerigars of all groups (including the control group-not vaccinated) did not demonstrate any signs of Newcastle Disease. They were refractory to the clinical disease with the NDV. Budgerigars from the control group (not vaccinated), showed antibody titers from HI test 13 and 19 days after challenge. Therefore, it was demonstrated the state of carrier of NDV in this species. The birds, from the vaccinated groups did not demonstrate genome viral excretion by RT-PCR and antibody titles were not detected by HI tests, respectively. It was also demonstrated the importance of the vaccination in the suppression of the state of carrier of NDV in budgerigars. © Asian Network for Scientific Information, 2013.
Keywords: Budgerigars; Melopsittacus undulatus; NDV carrier; Newcastle disease; Vaccination